Monocyte activation and gut barrier dysfunction in South African youth on antiretroviral therapy and their associations with endothelial dysfunction. (1st September 2020) - Dirajlal-Fargo, Sahera; Yu, Jiao; Albar, Zainab; Sattar, Abdus; Mahtab, Sana; Jao, Jennifer; Myer, Landon; Zar, Heather J.; McComsey, Grace A.
Abstract : Background: There is evidence for endothelial dysfunction in youth living with perinatally acquired HIV (YLPHIV). However, little data exist on its mechanisms. Methods: YLPHIV and age-matched HIV-uninfected (HIV−) youth enrolled in the Cape Town Adolescent Antiretroviral Cohort in South Africa between 9 and 14 years of age were included. YLPHIV were on antiretroviral therapy more than 6 months with viral load less than 400 copies/ml at baseline and 24 months. Serum biomarkers of systemic inflammation, monocyte activation, intestinal integrity, and oxidized LDL-cholesterol were measured at baseline and after 24 months. Endothelial function was measured at 24 months using reactive hyperemic index (RHI); endothelial dysfunction was defined as RHI less than 1.35. Spearman correlation coefficient and quantile regression were used to examine associations between RHI and different biomarkers. Results: We included 266 YLPHIV and 69 HIV− participants. At baseline, median (Q1, Q3) age was 12 (11, 13) years and 53% were females. YLPHIV had poorer endothelial function compared with HIV− youth (RHI = 1.36 vs. 1.52, P < 0.01). At baseline and 24 months, YLPHIV had higher markers of monocyte activation (soluble CD14), gut barrier dysfunction (intestinal fatty acid binding protein) and oxidized LDL-cholesterol ( P ⩽ 0.04) compared with HIV− youth. Among YLPHIV, soluble CD14 remained associated with endothelial dysfunction after adjusting for age, sex, Tanner stage, and antiretroviral therapy duration (β: −0.05, P = 0.01). Conclusion: Despite viral suppression, South African YLPHIV have poor endothelial function and persistent evidence of monocyte activation and gut barrier dysfunction compared with HIV− youth. The long-term clinical significance of gut integrity and monocyte activation needs to be further assessed in YLPHIV.